IMPACT OF WORK FACILITIES AND WORK WELFARE ON EMPLOYEE PERFORMANCE - Elisabet Simanungkalit; Mustika Dewi; Bambang Suseno (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The aim of this research is to find out the impact of work facilities and work welfare on the performance of employees of PT Garuda Mas Perkasa Medan. The type of research is quantitative, based on methods of collecting concrete data and decrypting relationships or influences between variables in research. The sample consisted of 100 respondents from PT Garuda Mas Perkasa Medan. The research uses probability and non-probability sampling techniques to gather data. Data collection techniques include questionnaires and interviews. Data analysis is done by conducting validity tests, reliability tests, and performing descriptive statistics. Classical assumptions by searching for normality, multicollinearity. The Multiple regression linear analysis with hypothesis testing. The result is a multiple-regression linear analysis: Y = 3,259 + 0. 464X1 + 0. 403X2 + e. The results of the study obtained showed that the facilities with work welfare had a positive and significant impact on performance. The conclusion of this study is that the effect of work facilities has a positive and significant impact on performance, the level of safety has a significant and positive effect on performance, and the simultan of the work facilities and work welfare has a significant influence on the effectiveness of employers at PT Garuda Mas Perkasa Medan.